Kepemimpinan Perempuan Dalam Dunia Perpustakaan: Tinjauan Terhadap Kepemimpinan Kepala Perpustakaan Perguruan Tinggi - Ramdhani Rosalia, Desfiana (Ilmu Informasi Perpustakaan dan Kearsipan, 2024)
This research endeavors to examine the unique leadership styles exhibited by women in the realm of libraries. The research methodology employed in this study relied heavily on the analysis of theoretical studies found in research journals, books, and other scholarly papers. The findings of studies on gender issues, in general, indicate that there are minimal disparities in terms of organizational aspects. However, when gender is associated with leadership style, it becomes evident that women possess a specific style of leadership, not due to inherent gender differences, but rather as a result of job characteristics and demands. This, in turn, highlights the significant influence of job characteristics on the leadership styles adopted by women. In the context of women's leadership styles and their relationship with job characteristics, two distinct categories emerge: feminist-masculine leadership styles and transformational-transactional leadership styles.